Damage Investigation in Composite Materials by Means of New Thermal Data Processing Procedures. (10th March 2016) - Palumbo, D.; Galietti, U.
Abstract: Stimulated thermography is a non‐destructive technique capable of detecting and quantifying defects in composite material thanks to the varying thermal behaviour they display if subjected to a thermal stimulation. Although in literature valid and consolidated thermographic techniques (lock‐in and pulsed/stepped thermography) are available, the use of stimulated thermography in industry is still not widespread in the case of application of large structures, mainly because of the overall lengthy time required for testing owing to the necessary scanning approach. In this work, the influence of the main set‐up parameters of stimulated thermography is assessed, analysing simulated defects on a sample specimen made of Glass Fiber Reinforced Polymer. In particular, the attention was focused on the optimisation of testing parameters for the improvement of signal quality and to reduce testing time. In this regard, a new procedure is proposed based on a least‐square fitting algorithm capable of providing various synergic thermal analyses with a modulated heat excitation and within a single test.